FOOD HABITS OF THE GREAT HORNED OWL (BUBO VIRGINIANUS) AND THE BARN OWL (TYTO ALBA) IN AN AGROECOSYSTEM OF ENTRE RÍOS, ARGENTINA (Natura Neotropicalis, 2018)
The Great Horned Owl (Bubo virginianus) and the Barn Owl (Tyto alba) are common nocturnal raptors of Argentina. However, there is no information on the diet of these raptors living in syntopy for the country. For this reason the aim of this contribution was to determine and compare the trophic habits of these raptors in a rural locality of Entre Ríos province. Their trophic overlap was also determined. B. virginianus consumed six species of mammals, one of amphibians and three of birds. T. alba consumed 10 species of mammals, one of amphibians and two of birds. There was a low value of dietary overlap and it was observed that the Great Horned Owl consumed larger prey than the Barn Owl.
Keywords: diet; raptors; diet overlap